The Role of Gamification on Purchase Intention in Users of Financial Technology Mobile Banking Applications - Damaresty Andyani; Rizal Edy Halim (Eduvest - Journal of Universal Studies, 2025)
Financial technology (fintech) has experienced rapid growth in recent years, with mobile banking being one of the main services widely adopted by Indonesians. One of the innovative strategies used in mobile banking applications is gamification, which is the application of game elements to increase user engagement and encourage positive financial behavior. This study aims to analyze how gamification elements, such as reward, competition, immersion, enjoyment, and sense of presence, influence the purchase intention of mobile banking app users in Indonesia. This study uses a quantitative method with a Structural Equation Modeling (SEM) approach to test the relationship between variables. Data was collected through a survey of mobile banking application users who have used gamification features in their financial transactions. The sample of this study amounted to 284 respondents with some specific criteria. The questionnaire was measured with a 7-point Likert scale. The findings provide implications for the fintech industry, particularly in developing effective gamification-based marketing strategies to increase user adoption and retention. The study also provides insights for app developers in designing interactive features that can strengthen user experience and encourage more active transaction behavior.